Pengaruh Belanja Pendidikan, Kesehatan, Dan Perlindungan Sosial Terhadap Ketimpangan Pendapatan Di Pulau Jawa - Anggun Aswita Putri; Muhammad Anshari (Universitas Negeri Padang, 2026)
Income inequality remains a major obstacle to economic development in Java, which has a high concentration of economic activities. This study aims to analyze the effect of government spending on education, health, and social protection on income inequality, with economic spending and GRDP as control variables, during 2015–2024. Panel data from six provinces were analyzed using beta regression because the dependent variable is the Gini ratio. The results show that spending on education and social protection has a positive and significant effect on inequality, while health spending and GRDP have a negative and significant effect. Economic spending as a control variable also has a positive significant effect. These findings indicate that government budget allocation and regional economic growth play a key role in income distribution and human and social development. Therefore, budget allocation should focus on targeting education and social protection programs effectively, integrated with productive economic policies to sustainably reduce income inequality.